Functional remediation in bipolar disorder: 1-year follow-up of neurocognitive and functional outcome. (January 2016) - Bonnin, C. M.; Torrent, C.; Arango, C.; Amann, B. L.; Solé, B.; González-Pinto, A.; Crespo, J. M.; Tabarés-Seisdedos, R.; Reinares, M.; Ayuso-Mateos, J. L.; García-Portilla, M. P.; Ibañez, Á.; et al.
Abstract : Background: Few randomised clinical trials have examined the efficacy of an intervention aimed at improving psychosocial functioning in bipolar disorder. Aims: To examine changes in psychosocial functioning in a group that has been enrolled in a functional remediation programme 1 year after baseline. Method: This was a multicentre, randomised, rater-masked clinical trial comparing three patient groups: functional remediation, psychoeducation and treatment as usual over 1-year follow-up. The primary outcome was change in psychosocial functioning measured by means of the Functioning Assessment Short Test (FAST). Group×time effects for overall psychosocial functioning were examined using repeated-measures ANOVA (trial registration NCT01370668). Results: There was a significant group×time interaction for overall psychosocial functioning, favouring patients in the functional remediation group ( F = 3.071, d.f. = 2, P = 0.049). Conclusions: Improvement in psychosocial functioning is maintained after 1-year follow-up in patients with bipolar disorder receiving functional remediation.